Activity of AcD and nonAcD cells during high-frequency network oscillations [data] - Hodapp, Alexander; Kaiser, Martin Erich; Thome, Christian; Ding, Lingjun; Rozov, Andrei; Klumpp, Matthias; Stevens, Nikolas; Stingl, Moritz; Sackmann, Tina; Lehmann, Nadja; Draguhn, Andreas; Burgalossi, Andrea; et al. (Universität, 2022)
Information processing in neuronal networks involves the recruitment of selected neurons into coordinated spatiotemporal activity patterns. This sp...
Gesehen am 29.09.2022
Keywords: Forschungsdaten; Datenbank